Why do clocks run clockwise? : and other imponderables - Feldman, David (New York, NY Harper & Row, 1987)
Ponder, if you will ...What is the difference between a kit and a caboodle?Why don't people get goose bumps on their faces?Where do houseflies go in the winter?What causes that ringing sound in your ears? Pop-culture guru David Feldman demystifies these topics and so much more in Why Do Clocks Run Clockwise? -- the unchallenged source of answers to civilization's most nagging questions. Part of the Imponderables® series and charmingly illustrated by Kassie Schwan, Why Do Clocks Run Clockwise? challenges readers with the knowledge about everyday life that encyclopedias, dictionaries, and almanacs just don't have. And think about it, where else are you going to get to the bottom of why hot dogs come ten to a package while hot dog buns come in eights?
Keywords: Questions and answers